Governance and human rights in construction safety: A systematic review on cause of accidents among foreign workers - Nurul Izzatul Hidayah, Saundi; Norhana, Mohd Aripin; Nur Sofia Nabila, Alimin; Azim Azuan, Osman (Penerbit Universiti Malaysia Pahang, 2025)
As workplace accidents, including fatalities, continue to pose a significant concern, especially within the construction sector and among foreign workers, it needs to be seriously addressed and promptly monitored. However, there is a notable lack ofcomprehensive reviews exploring the causes of accidents among foreign workers in the construction sector. Consequently, this research undertakes a systematic literature review with the following study objectives: (1) What are the underlying causes of construction accidents among foreign workers? And (2) What potential areas of research can be explored to mitigate accidents among foreign workers in the construction sector? The study follows a review protocol, formulates research questions, and systematically conducts searches using Scopus databases to ensure rigour and relevance in the analysis. The findings of the review demonstrate that language problems have a very significant connection with the construction sector which can cause accidents, followed by lack of safety training among foreign workers, cultural differences, poor communication, lack of safety knowledge, falls from height, and lack of experience as the causes of construction accidents among foreign workers. Furthermore, this paper provides valuable guidance and ideas for future researchers interested in exploring deeper into Sustainability Development Goals (SDGs) investigations in the construction sector.